2020
DOI: 10.1186/s12964-020-00654-2
|View full text |Cite
|
Sign up to set email alerts
|

LncRNAH19 improves insulin resistance in skeletal muscle by regulating heterogeneous nuclear ribonucleoprotein A1

Abstract: Background Skeletal muscle is essential for glucose and lipid metabolism. Growing evidence reveals the importance of long non-coding RNAs (LncRNAs) in metabolism. This study aimed to investigate the function of LncRNA H19 (H19) in lipid metabolism of skeletal muscle and its potential mechanisms. Methods Glucose tolerance, serum insulin and lipid content in serum and skeletal muscle were determined in control and H19-overexpressed db/… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 55 publications
1
25
0
2
Order By: Relevance
“…These processes are closely related to the genes PGC1a and CPT1b that reverse FFA-induced lipid accumulation and improve IR. 263 This suggests the complex effect of lncRNAs on the IR progression.…”
Section: The Insulin Signaling and Irmentioning
confidence: 99%
“…These processes are closely related to the genes PGC1a and CPT1b that reverse FFA-induced lipid accumulation and improve IR. 263 This suggests the complex effect of lncRNAs on the IR progression.…”
Section: The Insulin Signaling and Irmentioning
confidence: 99%
“…Additionally, it negatively regulates PPARγ at the translation and protein levels and inhibits the formation of lipid droplets in liver cells. In addition to regulating the growth and development of adipocytes, H19 improves insulin resistance by promoting fatty acid oxidation and reducing the accumulation of ectopic lipids in skeletal muscle by targeting hnRNPA1 [141].…”
Section: The Role Of Lncrna In Ectopic Fat Depositionmentioning
confidence: 99%
“…Additionally, the overexpression of H19 in muscle increased acetyl-CoA carboxylase 1 (ACC1) and cAMP-activated protein kinase (AMPK) phosphorylation and increased the expression of peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α), SIRT1, carnitine palmitoyltransferase 1b, and CD36, which suggests that H19 overexpression ameliorates glucose intolerance, dyslipidemia, and IR ( Figure 2 ). Furthermore, using RNA pull-down and immunoprecipitation assays, the authors identified the interaction of H19 with heterogeneous nuclear ribonucleoprotein A1 (hnRNPA1), which has been reported to play an important role in glucose and lipid metabolism [ 55 ].…”
Section: Lncrnas In Insulin Resistancementioning
confidence: 99%